Pengaruh Customer Experience, Customer Satisfaction dan Customer Bonding Terhadap Loyalitas Pelanggan Pada Mahasiswa FEB Angkatan 2019 Universitas Islam Malang Pelanggan Mie Gacoan Dinoyo Malang - Yulia Feby Aowahilwa; Budi Wahono; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In this modern era a lot of progress in the business world. Competition is so tight that every producer continues to develop its business to win the competition. One of them is a culinary business in the field of noodles, such as Mie Gacoan. In this research, the researcher chose Mie Gacoan Dinoyo Malang as the material to be studied. The purpose of this study was to determine and analyze the influence of customer experience, customer satisfaction and customer bonding on customer loyalty at Mie Gacoan Dinoyo Malang. The population in this study were FEB students class of 2019 at the Islamic University of Malang, customers of Dinoyo Malang Gacoan Noodles. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 70 respondents. The results of the study show that partially Customer Experience, Customer Satisfaction and Customer Bonding have a significant effect on Customer Loyalty. Meanwhile, simultaneously Customer Experience, Customer Satisfaction and Customer Bonding have a significant effect on Customer Loyalty. The results of this study can be used as a reference for further researchers by developing the variables studied and adding populations and samples to develop research. Keywords: Customer Experience, Customer Satisfaction, Customer Bonding, Customer Loyalty